2019
DOI: 10.1016/j.yjmcc.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibition as a therapeutic strategy in myocardial ischemia/reperfusion injury

Abstract: Reperfusion injury during myocardial infarction accounts for approximately half of final infarct size. Whereas this has been known for decades, efficacious therapy targeting reperfusion injury remains elusive. Many proteins are subject to reversible acetylation, and drugs targeting enzymes that govern these events have emerged in oncology. Among these, small molecules targeting protein deacetylating enzymes, so-called histone deacetylases, are approved for human use in rare cancers. Now, work emerging from mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Class I and II HDAC inhibitors represent a group of small molecule epigenetic modifiers that have demonstrated efficacy in animal models of heart failure over the last decade (Evans and Ferguson, 2018). HDAC inhibition has also been used as a therapeutic strategy for cardiac I/R injury (Xie et al, 2019). Emerging evidence also suggests that inhibition of HDACs protects the heart against myocardial injury and stimulates endogenous angiomyogenesis even in the diabetic heart (Bocchi et al, 2019).…”
Section: β-Ohb Is An Endogenous Hdac Inhibitor and Maintains Mitochondrial Homeostasismentioning
confidence: 99%
“…Class I and II HDAC inhibitors represent a group of small molecule epigenetic modifiers that have demonstrated efficacy in animal models of heart failure over the last decade (Evans and Ferguson, 2018). HDAC inhibition has also been used as a therapeutic strategy for cardiac I/R injury (Xie et al, 2019). Emerging evidence also suggests that inhibition of HDACs protects the heart against myocardial injury and stimulates endogenous angiomyogenesis even in the diabetic heart (Bocchi et al, 2019).…”
Section: β-Ohb Is An Endogenous Hdac Inhibitor and Maintains Mitochondrial Homeostasismentioning
confidence: 99%
“…Similar to our finding, the positive correlation between NFAT and HDACs was also certified by a recent study and was confirmed as key promoter in the regulation of inflammation during the preservation of islet function after islet transplantation [ 27 ]. Besides, inhibition of HDAC1 exerted a neuroprotective effect against cerebral IRI [ 28 , 29 ]. Furthermore, a prior study demonstrated that the increased expression of HDAC1 was partially responsible for the deterioration of mice with HIRI-like symptoms, and its repression acted as a promising therapeutic target for HIRI management [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the protective effect and therapeutic potential of HDACs were verified by cardiac disease pathogenesis, including suppressing cardiac fibrosis; enhancing angiogenesis; preventing electrical remodelling; and regulating apoptosis, autophagy, and cell cycle arrest (Chun, 2020). Studies exhibited that HDAC enzyme suppression has become a potential candidate for decreasing reperfusion impairment (Xie et al, 2019). Ting et al (Zhao et al, 2007) reported the use of trichostatin A (TSA) as an efficient HDAC inhibitor to imitate early pharmacologic preconditioning.…”
Section: Histone Modifications and Hdacs In MImentioning
confidence: 99%